Quiet eye training aids the long-term learning of throwing and catching in children: Preliminary evidence for a predictive control strategy. Issue 1 (2nd January 2017) - Miles, C. A. L.; Wood, G.; Vine, S. J.; Vickers, J. N.; Wilson, M. R.
Abstract: Quiet eye training (QET) may be a more effective method for teaching children to catch than traditional training (TT) methods, but it is unclear if the benefits accrued persist in the long term. Thirty children were randomly allocated into a QET or TT group and, while wearing a mobile eye tracker, underwent baseline testing, training and two retention tests over a period of eight weeks, using a validated throw and catch task. During training, movement-related information was provided to both groups, while the QET group received additional instruction to increase the duration of their targeting fixation (QE1) on the wall prior to the throw, and pursuit tracking (QE2) period on the ball prior to catching. In both immediate (R1) and delayed (R2, six weeks later) retention tests, the QET group had a significantly longer QE1 duration and an earlier and longer QE2 duration, compared to the TT group, who revealed no improvements. A performance advantage was also found for the QET compared to the TT group at both R1 and R2, revealing the relatively robust nature of the visuomotor alterations. Regression analyses suggested that only the duration of QE1 predicted variance in catch success post-training, pointing to the importance of a pre-programming visuomotor strategy for successful throw and catch performance.